Diagnóstico para que(m)? O cerceamento da transexualidade pelo discurso psiquiátrico - Carniel, Caio César Garcia (Universidade Federal de São Carlos, 2019)
A body which makes ruptures with stabilized bodies is constantly addressed to be silenced and eradications. Talking about the oneself, depending on governability, may be subject to death or/and other forms of control, especially when the speaker is a body marked by the trans-sexual matter. This research aims to show the scientific path given to the trans-body, especially in the Diagnostic and Statistical Manual of Mental Disorders (DSM), and to think about the effects this has on the identification processes of the subjects marked by the trans matter and also thinking about the normative effect - present in the manuals - within society. We begin by thinking about the psychiatric device, which sets up a network of practices that creates a pedagogy about bodies based on alliances between institutions and public policies [governability]. Thus, the device socially regulates the way in which the treatment of bodies will be addressed - especially the erratic bodies, which will permeate the pathological context. Once in the pathological shackles, it is possible to see the sieve that determines the division between the normal and the pathological, being represented, respectively, by the cisgender body and the transvestite indicating a heteronormativity regarding the treatment of the bodies in relation to their sexualities and genders. We have named this process - based on the Foucault’s theory - of subjection, that is, the 'making' of a subject, the regulation principle by which the subject is formulated and produced. However, according to Foucault's theory, all subjection – associate by a Power - provides its own material for the resistances raise, and with it, it’ll be possible to think of the identities’ failure created by subjection. Starting from some clinical cases, we will point out where the symptom-diagnosis relationship fails, showing the ruptures in the manuals prescriptive speech and pointing to a subjective dimension which provides a parrhesiastic act. The idea of parrhesia enters in order to point out the subjective veridiction which isn’t homologated by psychiatric discourse, but by the symptom that appears as an authentic revelation of self. And finally, the last step will be taken towards to the pointing out of the distance between the moral and prescriptive directions of the diagnosis manuals, and an approximate of an understanding about the symptom that considers the conditions of existence for it, leading us to a body recognition marked by a pragmatic, but maintaining a production of oneself - despite the pragmatics-of-oneself. Therefore, it’s possible to deliberate that the bodies marked by the trans(sexual) matter are captured by psychiatric discourse and they gain places of approval before society and suffer subjection on identity constructions. The place of resistance, such as "woman with a penis" - among other examples contained in this work – collapses the stabilized constructions about the feminine and the masculine, as well as the trans-sexuality’s definitions. Remarking, therefore, that an understanding about trans-sexuality is only possible in one-on-one. The ethical reading of oneself is only possible through the r-existence [resistance]
Diagnosis for who(m)? The certaining of transexaulity by psychiatric speech
Keywords: Transexualidade; Heteronormatividade; Sujeição; Resistência; Ética; Transsexuality; Heteronormativity; Subjection; Resistance; Ethic; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA